Like people in history - Picano, Felice (Viking, 1995)
A novel chronicling life in the homosexual world from the 1950s to the present. It focuses on the relationship of two cousins and their love for the same man, a Vietnam War hero. The novel describes the spirit of community which aids created; Neal A. Newfield, Ph.D., LICSW (Giver)